ИЗУЧЕНИЕ АЛЬГОФЛОРЫ РИСОВЫХ ПОЛЕЙ ШИЕЛИЙСКОГО РАЙОНА КЫЗЫЛОРДИНСКИЙ ОБЛАСТИ И ВЫДЕЛЕНИЕ БАКТЕРИОЛОГИЧЕСКИ ЧИСТЫХ КУЛЬТУР МИКРОВОДОРОСЛЕЙ И ЦИАНОБАКТЕРИЙ (Experimental biology, 2017)
In the rice fields Shiely district of Kyzylorda region was found 47 species and varieties of algae, including: euglenophytes - 1, green - 10 blue-green - 15, diatom - 21. Identified five bacteriological pure cultures of microalgae and cyanobacteria, and studied their morphological and cultural properties.
Keywords: rice; Shiely; Kyzylorda; microalgae; cyanobacteria